Diagnosis and management of lipoedema - a review paper - Małgorzata Szypłowska; Adrianna Gorecka; Adrian Kuś; Bartłomiej Zaremba; Michał Obel (Kazimierz Wielki University, 2020)
Lipoedema is a chronic progressive disorder of adipose tissue leading to an enlargement of lower extremities. It is considered to be rare; however, the prevalence of the disease is underestimated because it is commonly misdiagnosed as obesity or lymphedema and the general awareness is poor. The etiology of the disorder is considered to be multifarious, including genetic inheritance, hormonal imbalance and microcirculation alterations. Diagnosis is mainly based on medical history and physical examination. Management of lipoedema is focused on reducing the symptoms, improving the quality of life and preventing further progression of the disease. The aim of this paper is to raise the awareness of the disease and provide appropriate clinical guidance for the assessment of lipoedema. We searched through the PubMed/MEDLINE database and took into consideration all of the results available as of 6September, 2020 and outlined the current evidence regarding lipoedema epidemiology, etiology, clinical presentation, differential diagnosis, and management. Better understanding of lipoedema is crucial for establishing an early diagnosis and a proper treatment, which in turn will reduce the psychological and physical implications associated with the disease.